(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
The new crustacean microcoprolite, Favreina carpatica ,is described from the Middle Jurassic of Rucăr-Bran zone, South Carpathians. It is the ichnospecies with the highest number (about 280) of longitudinally arranged canals pasing through the rod-shaped microcoprolite. Favreina carpatica was found in reddish to brown-carbonate sediments.